Effects of Spirulina (Spirulina platensis) on production, hematological parameters and lipid profile in layers - Sarker, Md Sulayman; Rafiq, Kazi; Rahman, Md Mizanur; Ibne Khalil, Kazi Khalid; Islam, Md Sodrul; Islam, Md Shahidul (Research in Agriculture Livestock and Fisheries, 2022)
The experiment was conducted to evaluate the effects of spirulina on production, hematological parameters and lipid profile in layers. Thirty (30) layer birds of 65 weeks of age were randomly divided into three groups (A, B and C) containing 10 birds in each group. Birds were subjected to treatments for a period of 1 month (30 days) as per fol lowing schedule: Group-A treated with 2gm spirulina/kg feed; Group-B: treated with 4gm spirulina/kg feed and Group-C: without any treatment. With the supplementation of spirulina, feed consumption and body weight were not affected, but egg production was increased significantly. Results showed that total erythrocyte count (TEC), haemoglobin concentration and packed cell volume (PCV) were significantly higher (P<0.05) in treated groups compared to control. Serum total cholesterol (TG), triglyceride (TC)) and low density lipoprotein (LDL) cholesterol were significantly decreased, as well as HDL was increased (P<0.05) with addition of the increasing rate of spirulina supplemented groups (2gm and 4 gm.) than the control group. Overall, this work suggests that spirulina has a positive effect on egg production and explores the perspective use of spirulina improves haematological parameters and lipid profiles in layer birds. Res. Agric., Livest. Fish.9(1): 49-55, April 2022